OCLUSION SELECTIVA ARTERIAL EXTRAHEPATICA EN LOS TRAUMATISMOS GRAVES DELHIGADO NUESTRA EXPERIENCIA 1979-1990 - Núñez Huerta, Edgar (2024)
We describe our 10 year-experience in trealment of severe liver traumatic Injuries with selective extrahepatic arterial occluslon. Thls procedure done In 13 patients; lt was successful In 12 cases and falled In only 1 case. Post-operative hepatic complications were 23%; among the extrahepatic complicatlons, respiratory complications were 61.3%. Mortallty was caused by continuous hepatic bleeding In 7.6% of the patients; pancreatitis and neurologic injuries were the cause of death In 15.2 % or the cases. These experience proved that this procedure or hepatic hemostasis is highly reliable, associated to low-mortality, quickly, and applies either to inaccessible penetrating or nonpenetrating hepatic injuries, and also to those associated with gut injury. Besides, this procedure could be used when other hemostatlc methods have failed. Thls procedure can be developed by any trained surgeon and it does not require sophisticated instruments. This procedure should not be used for perihepatic vein injuries or non-mechanical bleeding.